Comparative Analysis Of Financial Performance Of Conventional Banking In Asean - Andria Putri Novita Erwanda; Idah Zuhroh; Eris Tri Kurniawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
ASEAN is a combination of 10 countries in Southeast Asia. Each ASEAN member country has a different banking system, but all are dominated by conventional banks which have an important role in the region's economic growth. This research aims to identify the influence of the NPL, CAR, and BOPO variables partially and simultaneously on ROA on the financial performance of conventional banking in ASEAN. Apart from that, this research also aims to compare differences in regulatory structures to identify the strengths and weaknesses of banks that show strong financial performance in facing challenges and to assist in evaluating systematic risks that may arise from the banking sector in ASEAN countries. The method used in the research is a quantitative method with a comparative or comparing approach, and the data was analyzed through a panel test using Eviews 12 software. The results of the hypothesis test showed that simultaneously, the three variables (NPL, CAR, and BOPO) significantly influence banking profitability in ASEAN (Indonesia, Malaysia, Singapore, and Vietnam).